2017
DOI: 10.1111/tpj.13477
|View full text |Cite
|
Sign up to set email alerts
|

A Gly65Val substitution in an actin, GhACT_LI1, disrupts cell polarity and F‐actin organization resulting in dwarf, lintless cotton plants

Abstract: Actin polymerizes to form part of the cytoskeleton and organize polar growth in all eukaryotic cells. Species with numerous actin genes are especially useful for the dissection of actin molecular function due to redundancy and neofunctionalization. Here, we investigated the role of a cotton (Gossypium hirsutum) actin gene in the organization of actin filaments in lobed cotyledon pavement cells and the highly elongated single-celled trichomes that comprise cotton lint fibers. Using mapping-by-sequencing, virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 64 publications
(84 reference statements)
1
44
0
Order By: Relevance
“…Subsequently, several Mendelian genes related to growth, disease resistance, and fiber development have been successfully identified in cotton. For instance, GhACT_LI1 [43], GoPGF [44], GhLMI1-D1b [45], GoSP [46], and GhLMMD [47] for fiber development, glandless phenotype, leaf shape, branching, and necrotic leaf damage have been cloned using the corresponding mutants, respectively.…”
Section: Map-based Cloningmentioning
confidence: 99%
“…Subsequently, several Mendelian genes related to growth, disease resistance, and fiber development have been successfully identified in cotton. For instance, GhACT_LI1 [43], GoPGF [44], GhLMI1-D1b [45], GoSP [46], and GhLMMD [47] for fiber development, glandless phenotype, leaf shape, branching, and necrotic leaf damage have been cloned using the corresponding mutants, respectively.…”
Section: Map-based Cloningmentioning
confidence: 99%
“…Fuzz fibers are usually <5 mm in length and remain attached to the seeds after ginning (Zhang et al, 2007;Mauney, 2015). Currently, numerous naturally occurring cotton fiber mutants have been identified globally and characterized at the genetic, gene expression, and, more recently, genetic mapping (map-based cloning) levels (Rong et al, 2005;Hinchliffe et al, 2011;Kim et al, 2013a;Wang et al, 2014a;Naoumkina et al, 2015;Hu et al, 2016;Wan et al, 2016;Thyssen et al, 2017;Zhu et al, 2018). It is worth noting that it is difficult and often unpractical to differentiate fuzz fibers from extremely short (<6 mm) lint fibers before or after ginning.…”
Section: Unraveling Cotton Fiber Development Using Fiber Mutants In Tmentioning
confidence: 99%
“…Complementary DNA microarray and candidate gene analysis based on the genome sequences of the diploid G. raimondii identified a handful of candidates including an actin near the Li 1 locus (Gilbert et al, 2014;Jiang et al, 2015). Using high-resolution genetic mapping, Thyssen et al (2017) reported that the causative gene of the Li 1 mutation is a substitution of glycine to valine at position 65 in the protein sequence of an actin gene, GhACT_LI1 (Gh_D04G0865). This alteration disrupts progressive elongation of F-actin, resulting in a disorganized cytoskeleton and reduced cell polarity, and consequently dwarf cotton plants with very short fibers.…”
Section: Actins and Annexins And Their Roles In Fiber Elongationmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant actin cytoskeleton plays crucial roles in diverse cellular processes, such as cell elongation, cell division, intracellular transportation and cell wall biosynthesis (Liu et al ). Growing evidence demonstrates that cell elongation and secondary wall synthesis are associated with the dynamic reorganization of both actin cytoskeleton and microtubules in developing cotton fibers (Quader et al ; Seagull ; Wang et al ; Han et al ; Thyssen et al ). A number of cytoskeletal genes were found to express preferentially in fiber cells, and some of them were shown to function in the regulation of fiber development (Li et al ; Wang et al ; Wang et al ; Han et al ; Zhang et al ).…”
mentioning
confidence: 99%